KRITIK NALAR ISLAM SEBAGAI METODE IJTIHAD : MEMBAHAS PEMIKIRAN MOHAMMED ARKOUN - Jamhari Jamhari (JIA (Jurnal Ilmu Agama), 2013)
Rational criticism of Islam that developed Arkoun in studying a problem or not text other is to get the "real substance" which may be knocked out, forgotten, or even not at all unthinkable, with the approach of linguistic, psychological, historical, and social and cultural anthropology. By referring to the style of thought Derrid, Paul Ricour, Michael Foucault, Pierre Bordue, in the field of language, Arkoun reveal diversity not previously seen and not said in the text. With the demolition was he trying to find the meaning of which is lost or created by the freezing process that afflicts thought Islam.Dengan deconstruction allows the things that have not occurred or even unthinkable to be revealed can be revealed. By restoring the purity of the teachings in accordance with the objectives desired by God (author). The primary objective reasoning criticism of Islam is to free thought of all sorts of images and imagery narrow, because it is not possible for Islamic reason to think clearly for such images still lingering in their reasoning. Rational criticism of Islam also aims to distinguish between revelation and history, transcendent revelation to restore the position of the original. This refund because they said there was a reduction in the value it contains after experiencing intermingling with human history (ideological, political, and interests). Here we need the critical stance, against all kinds of teologisme Islam (including all branches epistimologi like: fiqh, tafsir, the science of kalam, Aqeedah, and so on). Because after all, all it is a human creation as well, and we are entitled to put it on the table criticism.